Professionally important psychological qualities of successful managers of police organizations - V. Barko, Vadym; Okhrimenko, Ivan; Sashurina, Olena; Kryzhanovska, Olena; Butenko, Nadiia (Edelweiss Applied Science and Technology, 2024)
The research aims to investigate the professionally important psychological qualities of successful managers of police organizations. The research design is a cross-sectional study. The research was conducted in several stages during 2022-2023. The first stage involved a survey of police units personnel (n = 562) to identify “successful” managers; the second stage provided for the determination of the professionally important psychological qualities of successful managers of police organizations (n = 74) using a set of psychodiagnostic methods; the third stage made provisions for correlation analysis between the professionally important psychological qualities of successful managers. The following methods were used during the research: theoretical methods – analysis, synthesis, and generalization of scientific literature; empirical and psychodiagnostic methods – included a survey of police units personnel; methods of mathematical and statistical data processing. It was found that successful managers show high levels of working capacity, stress resistance, sociability, and proactive attitude. They are characterized by a sthenic type of reaction, pronounced motivation for personal achievement, and high levels of flexibility of thinking and creativity. They are also characterized by leadership and organizational qualities, and energy. The results of the research made it possible to form an idea of the professionally important psychological qualities of successful managers of police organizations, which will help to improve the professional selection of persons for managerial activities.